2007
DOI: 10.1172/jci31766
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of the transient receptor potential cation channel TRPV4 impairs murine bladder voiding

Abstract: Here we provide evidence for a critical role of the transient receptor potential cation channel, subfamily V, member 4 (TRPV4) in normal bladder function. Immunofluorescence demonstrated TRPV4 expression in mouse and rat urothelium and vascular endothelium, but not in other cell types of the bladder. Intracellular Ca 2+ measurements on urothelial cells isolated from mice revealed a TRPV4-dependent response to the selective TRPV4 agonist 4α-phorbol 12,13-didecanoate and to hypotonic cell swelling. Behavioral st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

24
351
2
2

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 295 publications
(379 citation statements)
references
References 50 publications
24
351
2
2
Order By: Relevance
“…1B were TRPV4 nonspecific. Similar nonspecific immunoreactivity has been reported in kidney sections of TRPV4 ϩ/ϩ and TRPV4 Ϫ/Ϫ mice probed with an antibody raised against the same C-terminal epitope of rat TRPV4 (29).…”
Section: Resultssupporting
confidence: 77%
See 2 more Smart Citations
“…1B were TRPV4 nonspecific. Similar nonspecific immunoreactivity has been reported in kidney sections of TRPV4 ϩ/ϩ and TRPV4 Ϫ/Ϫ mice probed with an antibody raised against the same C-terminal epitope of rat TRPV4 (29).…”
Section: Resultssupporting
confidence: 77%
“…The facts that 4␣PDD binds and activates TRPV4 (17) without the involvement of PKC (16) and that the response to 4␣PDD is totally lost in different TRPV4 Ϫ/Ϫ cells (ref. 29 and this study) strongly suggest that the 4␣PDD effects are mainly TRPV4-mediated, although we cannot completely rule out the participation of other pathways.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…In naive WT mice, we measured a regular pattern of pressure build-up and voiding ( Fig. 2A), as described previously (15). In comparison, cyclophosphamide-pretreated WT mice exhibited clear signs of pollakisuria, characterized by a doubling of the voiding frequency and an ∼50% reduction of the voided volume ( Fig.…”
Section: Development Of Cyclophosphamide-induced Cystitis In Wt Andmentioning
confidence: 64%
“…Recent research has shown that TRPV4, a cation channel of the transient receptor potential (TRP) superfamily (10,11), is highly expressed in the urothelial cell layer of the bladder, where it is implicated in sensing the filling state of the bladder (12)(13)(14)(15)(16). Importantly, Trpv4 −/− mice exhibited a lower voiding frequency and larger voided volume than wild type (WT) mice did.…”
mentioning
confidence: 99%